Comparative Study of Reinforced Concrete Beams in School Buildings Using Prestressed Concrete Beams - Petrus Haryanto Wibowo; Dony Dony (Journal of Civil Engineering and Planning (JCEP), 2022)
Building construction in Indonesia generally uses concrete. The concrete used for building structures, such as beams, generally utilizes reinforced concrete. It is very rare to see the use of prestressed concrete for building structures such as beams, especially in Batam City. This study aims to analyze the comparison between the beam structure with reinforced concrete that has been existing and prestressed concrete in the Kaliban School project. The stages in this research included prestressed concrete beam design and comparative analysis. The design of prestressed concrete beams was planned to be composite prestressed concrete blocks using the pre-tension method with a fully prestressed system, and was cast with the floor slabs and also supported during the casting period. Comparative analysis conducted by the researcher of this study was a comparison of the materials used in reinforced concrete beams and prestressed concrete beams. The results of the prestressed concrete structure design obtained a beam dimension of 200 × 400 with a diameter of 12.7 mm, in which 4 pieces were installed 125 mm below the beam. The results of the comparison analysis of the total material prices between prestressed concrete beams with dimensions of 200 × 400 and existing reinforced concrete beams with dimensions of 200 × 500 showed that prestressed concrete beams were 24.28% cheaper than reinforced concrete beams.